Multistakeholder Collaboration In Poverty Reduction In Surabaya City To Support The SDGs - Kurniawan, Yudiyanto Tri; Hidayanti, Henny (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Extreme poverty in Surabaya City is a multidimensional problem that requires sustainable intervention through collaboration between various parties. This study aims to analyze the existing conditions of the Labor-Intensive Program in Surabaya City as a poverty alleviation instrument in support of the Sustainable Development Goals (SDGs). Using a qualitative approach and Edi Suharto's 5P empowerment analysis, this study examines the program's processes of enabling, strengthening, protecting, supporting, and maintaining. The results indicate that the Labor-Intensive Program has successfully utilized unused government assets to create jobs for Beneficiary Families (KPM). The Surabaya City Government has integrated P3KE data through a barcode stickering system to ensure accurate targeting of aid. Functionally, this program has supported the achievement of SDG 1 (No Poverty) by increasing the purchasing power of beneficiaries (KPM) and SDG 8 (Decent Work and Economic Growth) through job creation at the grassroots level. However, the main challenges identified are economic sustainability and a "dependency mentality" on social assistance among beneficiaries. The study concluded that current multistakeholder synergy requires strengthening market protection and maintaining empowerment outcomes so that beneficiaries can achieve long-term economic independence and permanently escape the trap of extreme poverty.